2002
DOI: 10.1177/153331750201700310
|View full text |Cite
|
Sign up to set email alerts
|

Memories in the Making©: Outcome-based evaluation of an art program for individuals with dementing illnesses

Abstract: The author presents the results of a pilot project, an outcomes-based evaluation of Memories in the Making: An art program for individuals with dementing illnesses. Sponsored by the Greater Cincinnati Chapter of the Alzheimer's Association and implemented at adult day and nursing home sites, participants in the weekly art program use paints to express themselves by creating colorful visual images on paper or fabric. The individuals experienced pleasurable, sustained activity while engaged in making art. Utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 11 publications
1
79
0
3
Order By: Relevance
“…Beard points to the significant role that visual arts can play in the lives of people with dementia, as illustrated by several studies (Beard, 2012). Kinnsey and Rentz (Kinney & Rentz, 2005), expanding a previous pilot work (Rentz, 2002), assessed seven domains of well-being while subjects were participating in an art program for people with earlyonset or mid-stage dementia designed to promote self-expression through the visual arts. They also compared the well-being observed in the same individuals while participating in more traditional activities of the day center.…”
Section: Introductionmentioning
confidence: 99%
“…Beard points to the significant role that visual arts can play in the lives of people with dementia, as illustrated by several studies (Beard, 2012). Kinnsey and Rentz (Kinney & Rentz, 2005), expanding a previous pilot work (Rentz, 2002), assessed seven domains of well-being while subjects were participating in an art program for people with earlyonset or mid-stage dementia designed to promote self-expression through the visual arts. They also compared the well-being observed in the same individuals while participating in more traditional activities of the day center.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals engaged in this program are guided by trained facilitators to recreate memories, tell stories, and socialize through expression with watercolors and acrylics on various papers [ 46 ]. By expressing pleasure verbally and nonverbally, individuals demonstrate increased self-esteem with having created something of value to self and others [ 46 ].…”
Section: Creative Art Approachesmentioning
confidence: 99%
“…However a later review of the dementia literature [12] identified at least 11 measures of Quality of Life, or wellbeing. The study's analysis of the pyschometric properties, correlation with other methods, sensitivity to change and practical utility singled out the Greater Cincinnati Chapter Well-Being Tool [13] as best, but noted that the more recently developed AwareCare [14] also showed superior results as well as being freely available online (http://reach.bangor.ac.uk/AwareCare.pdf).…”
Section: A What Devices Can and Cannot Domentioning
confidence: 99%